Siting strategy of new tidal stations in the Bohai Sea using adjoint method - Wang, Haitang; Jiao, Shengyi; Lv, Xianqing (Frontiers in Marine Science, 2022)
The optimal siting selection strategy for new tidal stations in the Bohai Sea is investigated using a two-dimensional tidal model with the adjoint method. Harmonic constants (HCs) of the M2 constituent at all computing grids are estimated in the Bohai Sea by assimilating observations from existing tidal stations and altimeter data processed by X-Track software. Several grid points on the coastline are selected as new tidal station sites, and different combinations of selected points are regarded as different siting strategies. The HCs at these new tidal stations are served as “simulated observations” (SOs) which are assimilated into the tidal model to re-estimate the HCs in the Bohai Sea. Through comparisons between the re-estimated HCs and SOs, we can evaluate the effects of different siting strategies. Divide the Bohai Sea into different subdomains, numerical experiments are constructed to investigate the effects of different strategies in different subdomains, while the effects of schemes including inversion variables and different tidal constituents on siting selection are experimented. By analyzing the root-mean-square (RMS) difference between re-estimated HCs and SOs on the coastline in different subdomains, the optimum strategy for siting of new tidal stations in the Bohai Sea is obtained.